Key Determinants of Technology Adoption in Construction Projects in Magelang - Ety Fitriyani; Hulfa Istikomah; Abul Fida Ismaili; Bina Arumbinang Wajdi (G-Tech: Jurnal Teknologi Terapan, 2025)
The development of the construction sector in Indonesia is expected to increase annually.  Magelang had various large construction projects with a completion target of 2024. However, the use of construction technology in this region is limited resulting in delays in work, increased costs, and decreased quality. This study aims to identify, analyze, and rank factors influencing the use of technology in construction projects in Magelang based on their level of importance. Understanding those factors can help identify the right strategy to increase the wider and optimal adoption of technology in the construction sector for effective and efficient implementation. Data were collected by distributing questionnaires. The questionnaire consisted of 30 factors influencing the use of technology classified into three main categories: (1) human/workforce, (2) industry, and (3) management. This study found the first rank for each category, namely "lack of experience in using technology software" (human/labor category), "Availability of materials and ease of handling" (Industry category), and "Willingness of owners, supervisors, builders, and suppliers to participate in information management" (management category). Construction industry practitioners can utilize the findings of this study in developing systems to improve technological adoption in construction projects for more effective and efficient project implementation.